Dietary Fruit and Vegetable Supplementation Suppresses Diet-induced Atherosclerosis in LDL Receptor Knockout Mice (OR24-07-19). (13th June 2019) - Guo, Weimin; Kim, Sharon; Wu, Dayong; Li, Lijun; Thomas, Michael; Meydani, Simin; Meydani, Mohsen
Abstract: Objectives: Epidemiological studies have shown that consumption of fruits and vegetables (F&V) is inversely associated with incidence of cardiovascular disease (CVD). However, the evidence for causality and underlying mechanisms is lacking. Our objective was to determine if increased consumption of F&V could prevent atherosclerosis and its underlying mechanisms. Methods: A unique blend of the most commonly consumed 24 F&V was freeze-dried into a powder and mixed into diets. Thirty six 4-week old male LDL receptor knockout mice were randomly assigned to one of 3 diet groups (12/group): low fat (LF, 10 kcal% fat), high-fat (27 kcal% fat) with 0% F&V (HF), and HF plus 15% F&V diet (HF + FV, equivalent to 8–9 servings for humans). After 20 weeks, mice were euthanized and blood, aorta, and liver tissue were collected. Aortic atherosclerotic lesion, hepatic steatosis, plasma lipid profile and pro-inflammatory cytokine levels were measured. Results: No significant differences were found in body weight among the 3 groups. Mice fed HF diet had larger aortic atherosclerotic lesion and hepatic steatosis area than mice fed LF diet by 6.5 and 1.9 fold, respectively (p < 0.001). HF + FV group had 80% less aortic lesion and hepatic steatosis than HF group (p < 0.001). Mice fed HF diet had significantly higher plasma TG and LDL and lower HDL levels than mice fed LF diet, and this dyslipidemia was prevented by F&V supplementation. Further, HF + FV group had lower plasma TNFα levels compared to HF0 group (p < 0.05). Spearman correlation analysis showed that aortic atherosclerotic lesion and hepatic steatosis area were negatively correlated with plasma HDL (p < 0.001) and significantly and positively correlated with TNFα, and the ratios of LDL/HDL, TG/HDL, and non HDL/HDL. Conclusions: Our results demonstrate a causal role of high intake of F&V in preventing HF-induced atherosclerosis and hepatic steatosis, which may be mediated through improved dyslipidemia and reduced inflammation. Funding Sources: U.S. Department of Agriculture – Agricultural Research Service.